WMN-PSOSA: an intelligent hybrid simulation system for WMNs and its performance evaluations. (21st October 2019) - Sakamoto, Shinji; Barolli, Leonard; Okamoto, Shusuke
Networks of today are going through a rapid evolution. Recently, many new networks, especially wireless networks, are appearing. The wireless mesh networks (WMNs) are wireless networks having mesh topology. They have many advantages, such as high robustness and easiness for maintenance. However, WMNs have some problems that need to be solved. One important problem for WMNs is the node placement problem, which is an NP-hard problem. In this work, we propose and implement an intelligent hybrid simulation system based on particle swarm optimisation (PSO) and simulated annealing (SA) for node placement problem in WMNs, called WMN-PSOSA. We evaluate the performance of WMN-PSOSA system considering different distributions of mesh clients such as Weibull, chi-square, and uniform distributions. The simulation results show that the WMN-PSOSA performs better for Weibull distribution compared with the case of chi-square and uniform distributions.